Motivation For The Application Of Tqm In The Institutes Of Science And Technology Of Physical And Sports Activities - Metarfi, Khemissi; Merniz, Amina (Université de M'sila, 2019)
The aim of this study was to find out the rationale behind the application of TQM in the institutes of science and technology of physical and sports activities from the point of view of administrators at the Institute of Science and Technology of physical and sports activities at the University of M’sila. The study relied on the analytical descriptive approach as it fits the subject of the study. On a research sample consisting of 31 employees of the Institute of Science and Technology of physical and sports activities at the University of M’sila. • All the hypotheses have been achieved for the Administrative Institute of Science and Technology of physical and sports activities at the University of M’sila. هدفت هذه الدراسة إلى معرفة المبررات الدافعة لتطبيق إدارة الجودة الشاملة في معاهد علوم وتقنيات النشاطات البدنية والرياضية من وجهة نظر الإداريين في معهد علوم وتقنيات نشاطات البدنية والرياضية بجامعة المسيلة، اعتمدت الدراسة على المنهج الوصفي التحليلي كونه يتلاءم مع موضوع الدراسة، و استخدم الباحث الاستبيان و طبق على عينة بحث مكون من 31 موظف العاملين بمعهد علوم وتقنيات النشاطات البدنية والرياضية بجامعة المسيلة . و قد أوضحت النتائج المتوصلة إليها: أن جميع الفرضيات تحققت بالنسبة للإداري معهد علوم وتقنيات نشاطات البدنية والرياضية بجامعة المسيلة.
Keywords: TQM ; Higher Education ; Total Quality Justifications